the Role of Islamic Banking And transformasion Leadership in the Development of Halal Industry: an overview of financing and policy - Fatmawati, Fatmawati; Siradjuddin, Siradjuddin; Awaluddin, Muartiadi; Iswandi, Heri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
. The halal industry has become a driver of global economic growth with growing market potential, spanning the food, fashion, cosmetics, pharmaceutical, and tourism sectors. In this context, Islamic banking plays a strategic role as a provider of Sharia-compliant financing to support the growth of the halal value chain. However, challenges such as limited access to financing, low financial literacy, and suboptimal policy coordination between sectors continue to hamper strong integration between Islamic banking and the halal industry. This article aims to examine the role of Islamic banking and transformational leadership in driving the growth of the halal industry, focusing on two main aspects: the financing mechanisms implemented by Islamic financial institutions and the policy synergy between Islamic banks, regulators, and halal industry players. A qualitative approach using literature studies is used to elaborate on the relationship between leadership innovation, Islamic financial instruments, and regulatory support in strengthening the halal ecosystem. The study results indicate that transformational leadership in Islamic banking is expected to be able to create pro-halal internal policies, collaborate with halal regulators (BPJPH, DSN-MUI, KNEKS), strengthen GCG and ethical values in financing that focus on empowering halal MSMEs sustainably